(3GdQSGdI GdTeSjIs ((3YeQ Hf eMehO Hf Ydj s)
(3ChdgG (B:s
(3TQjaI hfcJ dWjaI ef YfOj ZjQ JGHY dCMO ef GdNdGFb s
(3BNQgG (B:s
(3hJSei GdbVjI MjfFP KdGKjI hbO jMPa GdQGHWI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs